Cultural unconscious in research: integrating multicultural and depth paradigms in qualitative research. Issue 5 (November 2016) - Yakushko, Oksana; Miles, Pekti; Rajan, Indhushree; Bujko, Biljana; Thomas, Douglas
Abstract: Culturally focused research has gained momentum in many disciplines, including psychology. However, much of this research fails to pay attention to the unconscious dynamics that underlie the study of culture and culturally influenced human beings. Such dynamics may be especially significant when issues of marginalization and oppression are present. Therefore, this paper seeks to contribute a framework for understanding cultural dynamics, especially unconscious cultural dynamics, within depth psychological qualitative research influenced by Jungian and post‐Jungian scholarship. Inquiry that is approached with a commitment to making the unconscious conscious seeks to empower and liberate not only the subject/object studied but also the researchers themselves. Following a brief review of multiculturalism in the context of analytically informed psychology, this paper offers several case examples that focus on researchers' integration of awareness of the cultural unconscious in their study of cultural beings and topics.